Fabrication and embedded sensors characterization of a micromachined water-propellant vaporizing liquid microthruster. (April 2021) - Fontanarosa, Donato; De Pascali, Chiara; De Giorgi, Maria Grazia; Siciliano, P.; Ficarella, Antonio; Francioso, Luca
Highlights: Sensorized Si-based water-propellant Vaporizing Liquid Microthurster. Embedded Temperature and Vapor Fraction Sensors for flow instability control. Sensor signals correlated to optical acquisition of flow within the microchannels. In-channel water vaporization enhanced by microtextured substrate. Reliable measurement of vaporization level inside each channel. Abstract: Rapid advances in micro/nanotechnology have enabled to achieve high levels of miniaturization, promoting the development of low cost and highly efficient microsystems for specific applications. In the space sector, the miniaturization of satellites has led to a renewed interest in the research and development of advanced micro-propulsion technologies able to generate small and accurate thrust forces and high specific impulse. This work presents the design and fabrication of a silicon-based water-propellant Vaporizing Liquid Microthurster (VLM) equipped with embedded microsensors for real-time monitoring of in-channel vapor/liquid fraction and fluid temperature during its operation. Anisotropic dry etching of silicon wafer and thermo-compressive bonding were chosen as key fabrication steps: the former process was used to better control the surface roughness on microchannels inner walls, the latter was used to guarantee the fluidic tightness and complete the fabrication process of the device. Borofloat 33 glass, used to seal the micromachined silicon wafer, allows the optical inspection of the fluid flow and vaporization within the different chambers during the device operation. A platinum resistive heater placed on the bottom of the chip was exploited for the heating of the propellant. A set of Resistive Temperature Detectors (RTDs) and, for the first time, capacitive sensors were designed and integrated inside the microthruster chip to add distributed sensing capabilities for flow instability control. Further, a secondary low-power platinum thin film resistive heater was placed inside each of the eight channels, in order to allow for localized precision fluid heating and flow control. The operational feasibility of the fabricated microthruster was assessed by means of a preliminary characterization of the embedded sensors, based on experimental tests supported by numerical investigations; the results demonstrated that the designed microsensor devices are able to maximize the microthruster efficiency, in terms of microtexture-enhanced in-channel water vaporization and reduced power consumption.